Design, Synthesis, and Antimicrobial Activity Evaluation of Ciprofloxacin—Indole Hybrids - Mingxia Song; Yi Hua; Yuxin Liu; Xunli Xiao; Haihong Yu; Xianqing Deng (Molecules, 2023)
With the overuse and misuse of antimicrobial drugs, antibacterial resistance is becoming a critical global health problem. New antibacterial agents are effective measures for overcoming the crisis of drug resistance. In this paper, a novel set of ciprofloxacin-indole/acetophenone hybrids was designed, synthesized, and structurally elucidated with the help of NMR and high-resolution mass spectrometry. The in vitro antibacterial activities of these hybrids against gram-positive and gram-negative pathogens, including four multidrug-resistant clinical isolates, were evaluated and compared with those of the parent drug ciprofloxacin (CIP). All the target compounds (MIC = 0.0625–32 μg/mL) exhibited excellent inhibitory activity against the strains tested. Among them, 3a (MIC = 0.25–8 μg/mL) showed comparable or slightly less potent activity than CIP. The most active hybrid, 8b (MIC = 0.0626–1 μg/mL), showed equal or higher activity than CIP. Moreover, compound 8b showed superior bactericidal capability to CIP, with undetectably low resistance frequencies. Furthermore, molecular docking studies conducted showed that 8b and CIP had a similar binding mode to DNA gyrase (Staphylocouccus aureus). Thus, hybrids 3a and 8b could act as a platform for further investigations.